2005
DOI: 10.1016/j.ejcts.2004.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The GP IIb/IIIa inhibitor abciximab (ReoPro) decreases activation and interaction of platelets and leukocytes during in vitro cardiopulmonary bypass simulation

Abstract: Abciximab inhibits CPB-induced activation, interaction and consumption of platelets and leukocytes in vitro. GP IIb/IIIa inhibition should be considered as a promising approach not only to conserve platelet function but also to inhibit pro-inflammatory events during CPB in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
1
21
1
Order By: Relevance
“…Concerning abciximab, Straub and co-workers showed that abciximab treatment is associated with significantly lower number of platelet-leukocyte aggregates, lower Pselectin expression, and higher platelet and leukocyte count, using a heart-lung machine model [14]. The authors explain these results with abciximab cross-reactivity with Mac-1 and vitronectin receptors on leucocyte surface.…”
Section: Platelet Activation During Cardiopulmonary Bypassmentioning
confidence: 89%
See 3 more Smart Citations
“…Concerning abciximab, Straub and co-workers showed that abciximab treatment is associated with significantly lower number of platelet-leukocyte aggregates, lower Pselectin expression, and higher platelet and leukocyte count, using a heart-lung machine model [14]. The authors explain these results with abciximab cross-reactivity with Mac-1 and vitronectin receptors on leucocyte surface.…”
Section: Platelet Activation During Cardiopulmonary Bypassmentioning
confidence: 89%
“…Moreover, it causes inhibition of platelet P-selectin expression, decreasing binding capacity of platelets with leucocytes [13]. In contrast with tirofiban and eptifibatide, abciximab cross-reacts with Mac-1 and vitronectin receptors on leucocyte surface, probably attenuating local inflammation [14]. Abciximab is administered with an i.v.…”
Section: Pharmacology Of Gp Iib/iiia Inhibitorsmentioning
confidence: 98%
See 2 more Smart Citations
“…In an elegant revision, Erkan and Lockshin described the most recent studies related to inhibition of platelet aggregation [108], which included: 1) the simultaneous administration of anti-GPIIb/IIIa monoclonal antibodies and aPL in mouse models of APS, which resulted in smaller thrombus formation compared with aPL administration only [109]; 2) the prevention of aPL-mediated thrombosis in GPIIb/IIIa deficient mice [110]; and 3) the use of abciximab (a GPIIb/IIIa receptor inhibitor) in the treatment of acute thrombotic syndromes, such as myocardial infarctions and strokes [111]. No data on the use of GPIIa/ IIIb receptor inhibitors in APS patients exist, apart from limited data from an uncontrolled study of hydroxychloroquine, which might inhibit aPL-induced GPIIa/IIIB receptor expression [109].…”
Section: Specific Gpiib/iiia Antagonists and Other Anti-platelet Drugsmentioning
confidence: 99%